Recent advanced biotechnological strategies to enhance photo-fermentative biohydrogen production by purple non-sulphur bacteria: An overview. (5th May 2020) - Tiang, Ming Foong; Fitri Hanipa, Muhammad Alif; Abdul, Peer Mohamed; Jahim, Jamaliah M.d.; Mahmod, Safa Senan; Takriff, Mohd Sobri; Lay, Chyi-How; Reungsang, Alisara; Wu, Shu-Yii
Abstract: Photo-fermentation seems to be an attractive hydrogen production pathway. However, the light conversion efficiency and photo-hydrogen production of purple non-sulphur bacteria (PNSB) are very low, and hence, various biotechnological approaches are investigated to improve biohydrogen production. This article presents an overview of the advanced biotechnological approaches to enhance the photo-fermentative biohydrogen production. The advancements reviewed include optimisation of the medium, abiotic factors, the lighting regime, immobilisation techniques, application of photoluminating nanomaterials, genetic engineering, and other strategies. These approaches show positive results in the enhancement of photo-hydrogen production by PNSB. Some recommendations are suggested for further studies in the enhancement of photo-hydrogen production, such as green nanomaterials application, integrated dark- and photo-fermentation, genetic manipulation, and the application of the non-technological analysis approaches. Highlights: Various biotechnological approaches applied on photo-fermentation are reviewed. H2 yield improved by optimisation on medium, abiotic factors and lighting regime. Novel photoluminating nanomaterials is promising to increase H2 yield. Additional H2 enhancement strategies are recommended for further research.